2018
DOI: 10.1186/s13054-018-2086-x
|View full text |Cite
|
Sign up to set email alerts
|

Early fibrinogen concentrate therapy for major haemorrhage in trauma (E-FIT 1): results from a UK multi-centre, randomised, double blind, placebo-controlled pilot trial

Abstract: BackgroundThere is increasing interest in the timely administration of concentrated sources of fibrinogen to patients with major traumatic bleeding. Following evaluation of early cryoprecipitate in the CRYOSTAT 1 trial, we explored the use of fibrinogen concentrate, which may have advantages of more rapid administration in acute haemorrhage. The aims of this pragmatic study were to assess the feasibility of fibrinogen concentrate administration within 45 minutes of hospital admission and to quantify efficacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 28 publications
4
82
1
3
Order By: Relevance
“…Depletion is associated with poor outcomes, an effect which can be reversed with supplementation . Low fibrinogen concentrations correlate with increased transfusions, ventilator days, and increased early and late mortality . Fibrinogen supplementation improves clot initiation and stability, and may decrease mortality in this group .…”
Section: Current Understanding Of the Mechanisms Of Trauma‐induced Comentioning
confidence: 99%
“…Depletion is associated with poor outcomes, an effect which can be reversed with supplementation . Low fibrinogen concentrations correlate with increased transfusions, ventilator days, and increased early and late mortality . Fibrinogen supplementation improves clot initiation and stability, and may decrease mortality in this group .…”
Section: Current Understanding Of the Mechanisms Of Trauma‐induced Comentioning
confidence: 99%
“…While there is no evidence proving a difference in efficacy between cryoprecipitate and FC, there are practical factors that may allow more rapid administration in clinical practice. A number of studies have investigated the time to administration of fibrinogen replacement and have compared FC to cryoprecipitate but as yet there have been no large studies powered for patient‐centred outcomes or reduction in blood product usage . Systems that achieve early and rapid fibrinogen replacement generally involve empiric delivery of FC to patients presenting with clinical indications of severe bleeding, not those exclusively with a low fibrinogen level .…”
Section: Methodsmentioning
confidence: 99%
“…First, only two trials have been performed to determine the most effective dosing strategy (e.g., fixed dose vs. weight based vs. targeted to a postinfusion fibrinogen level): an RCT in postpartum hemorrhage found no impact of 2 g of fibrinogen, suggesting the minimum required dose is more than 2 g, and a trial in major pediatric surgery found earlier dosing of fibrinogen concentrate (at a higher FIBTEM maximum clot firmness threshold) was more effective in reducing transfusion requirements . Second, the preemptive use of fibrinogen concentrate before or early in the course of hemorrhage has been tested in only several small pilot trials, and a large definitive trial in severe traumatic hemorrhage is under way with cryoprecipitate (CRYOSTAT‐2/ISRCTN14998314). Overall, the preemptive use of fibrinogen before hemorrhage occurs has not been successful .…”
Section: Fibrinogen Concentratementioning
confidence: 99%